EFFECT OF CORE MUSCLE EXERCISE IN IMPROVING REACHING ACTIVITIES IN PATICIPANTS WITH HEMIPLEGIA - Dr.A.KUMARESAN,; Dr.J.ANTON MAHIBA, (International Journal of Pharma and Bio Sciences, 2016)
Experimental study design was used in this study. Total 40 patients were selected and divided into 2 equal groups (Group A& B).Pre-test values were measured by using Multi-directional reach test as outcome measure and were given conventional therapy for Group A and conventional therapy along with core strengthening exercise for 4 weeks and 5 days per week.The collected data was tabulated & analyzed using paired and un paired t test were used. Paired t-test was used to analyze significant changes between pre-test & post-test measurements in the group. Unpaired t-test was used to analyze significant changes between post-test measurements in between the groups. There was a significant difference between the groups. From this study it is concluded that the addition of core muscle exercises along with conventional set of exercises in hemiplegic patients will improve the dynamic balance.